Avenida Paulista as cultural heritage and the cultural heritage of Avenida Paulista - de Oliveira, Ana Claudia; Altamirano, Micaela (E|C, 2021)
Avenida Paulista (Paulista Avenue), a highly visible territory in the city of São Paulo, Brazil, has established itself as an urban icon and it is considered one of the main symbols of the city. Its history and constitution reflect different moments in the urban expansion of a city marked by permanent transformation. Factors such as popular appropriation, the mix of activities, as well as the various transformations of the cityscape ensured this place a dynamic and plural identity and has kept it representative of São Paulo’s society. Assuming that Avenida Paulista is a heritage site for São Paulo, this article is based on the premises of the French semiotic theory to analyze whether there is an articulation of meanings between the monuments and narratives sanctioned by the public authorities along its extension and the life practices that take place there. In addition to the on-site record, the choice of the corpus considers information from GeoSampa, the city’s official digital map platform.